2021
DOI: 10.3389/fspor.2021.687365
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cancer Related Fatigue, Physical Activity Related Health Competence, and Leisure Time Physical Activity in Cancer Patients and Survivors

Abstract: Background: A large body of evidence supports the positive effects of leisure time physical activity (LTPA) and exercise on cancer survivors. However, only a fraction of survivors manages to attain international PA recommendations. This can be attributed to several external and internal barriers toward PA those patients seem to encounter, with cancer related fatigue (CRF) being the most reported internal barrier. Nevertheless, self-efficacy and knowledge about the utilization of LTPA can serve as facilitators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Regarding the positive association of PAHCO and PA, our results are in accordance with our previous study in cancer patients, in which small to moderate positive associations between PAHCO dimensions and PA could be observed [ 26 ]. Further, the highest amount of PA was observed by individuals with high levels of self-regulation competence [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Regarding the positive association of PAHCO and PA, our results are in accordance with our previous study in cancer patients, in which small to moderate positive associations between PAHCO dimensions and PA could be observed [ 26 ]. Further, the highest amount of PA was observed by individuals with high levels of self-regulation competence [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finding corresponds with the low CC displayed in our analysis in P-profiles two and three, which incorporates 54% of the sample. Comparing the PAHCO levels to our cohort of 398 mixed cancer patients from the USA, our German MM patients have lower levels of MR (75 vs 67), a comparable level of CC (67 vs 67), and a higher level of SC (44 vs 67) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that the muscle of smokers are weaker and less fatigue‐resistant than those of nonsmokers 48 . Patients with high‐intensity physical activity at baseline reported less cognitive fatigue due to improved physical function and endurance to fatigue 49–51 . The results indicated that lifestyles may play an important role in the development of fatigue and should be considered in further intervention studies.…”
Section: Discussionmentioning
confidence: 97%